Sum of Bernoulli Numbers by Power of Two and Binomial Coefficient/Proof 1
Jump to navigation
Jump to search
Theorem
Let $n \in \Z_{>0}$ be a (strictly) positive integer.
Then:
\(\ds \sum_{k \mathop = 1}^n \dbinom {2 n + 1} {2 k} 2^{2 k} B_{2 k}\) | \(=\) | \(\ds \binom {2 n + 1} 2 2^2 B_2 + \binom {2 n + 1} 4 2^4 B_4 + \binom {2 n + 1} 6 2^6 B_6 + \cdots\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds 2 n\) |
where $B_n$ denotes the $n$th Bernoulli number.
Proof
Let $B_k$ denote the kth Bernoulli number
Let $B_k \left(x\right)$ denote the kth Bernoulli polynomial
By Value of Odd Bernoulli Polynomial at One Half:
\(\ds B_{2 n + 1} \left({\frac 1 2}\right)\) | \(=\) | \(\ds 0\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \sum_{k \mathop = 0}^{2 n + 1} \binom {2 n + 1} k B_k \left({\frac 1 2}\right)^{2 n + 1 - k}\) | \(=\) | \(\ds 0\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds 2^{2 n + 1} \sum_{k \mathop = 0}^{2 n + 1} \binom {2 n + 1} k B_k \left({\frac 1 2}\right)^{2 n + 1 - k}\) | \(=\) | \(\ds 0\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \sum_{k \mathop = 0}^{2 n + 1} \binom {2 n + 1} k B_k \left({\frac 1 2}\right)^{-k}\) | \(=\) | \(\ds 0\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \sum_{k \mathop = 0}^{2 n + 1} \binom {2 n + 1} k B_k 2^k\) | \(=\) | \(\ds 0\) |
By Odd Bernoulli Numbers Vanish:
\(\ds \sum_{k \mathop = 0}^{2 n + 1} \binom {2 n + 1} k B_k 2^k\) | \(=\) | \(\ds \left({2 n + 1}\right) 2 B_1 + \sum_{k \mathop = 0}^n \binom {2 n + 1} {2 k} B_{2 k} 2^{2 k}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds -\left({2 n + 1}\right) + \sum_{k \mathop = 0}^n \binom {2 n + 1 } {2 k} B_{2 k} 2^{2 k}\) | $B_1 = -\frac 1 2$ | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \sum_{k \mathop = 0}^n \binom {2 n + 1} {2 k} B_{2 k} 2^{2 k}\) | \(=\) | \(\ds 2 n + 1\) | |||||||||||
\(\ds \leadsto \ \ \) | \(\ds \sum_{k \mathop = 1}^n \binom {2 n + 1} {2 k} B_{2 k} 2^{2 k}\) | \(=\) | \(\ds 2 n + 1 - B_0\) | |||||||||||
\(\ds \) | \(=\) | \(\ds 2 n\) | $B_0 = 1$ |
$\blacksquare$